Family perceptions and coping strategies in cases of intersexuality: understanding their significance - Medeiros Rocha Santos, Moara De; Cavalcanti Ferreira de Araujo, Tereza Cristina (The Spanish Journal of Psychology, 2008)
Considering that the intersexual condition has a negative impact on the individual, their family, and society, health professionals and researchers have dedicated themselves to studying and assisting families faced with such an experience. The purpose of this study is to describe and understand the perceptions of primary caregivers regarding intersexuality and its developmental aspects. Six mothers and one grandmother of school age children were interviewed. The data indicated that living with the stigma of intersexuality can mean a permanent state of crisis within the family system. Issues such as guilt about the child’s suffering and questions related to the choice of gender follow the family from the moment of diagnosis. It is suggested that the therapeutic follow-up should foster the necessary conditions for the family group to be organized as a model of competence, replacing the model of guilt.